Policy and principal turnover: The impact of the Texas special education cap - Mandel, Zoë; Pendola, Andrew (Education Policy Analysis Archives, 2021)
Accountability policies in education play a significant role for the principals tasked with facilitating the implementation of these reforms at the school-level. While these policies are most often intended to improve student outcomes, this is not always the case. In some instances, these policies can prove detrimental to schools, yet principals are still responsible for compliance. In Texas, a federal investigation found the Texas Education Agency (TEA) was restricting access to special education services by incentivizing districts to enroll fewer than 8.5% of students, utilizing these numbers as a measure of district performance. The implementation of the “8.5% cap” in 2004 resulted in a sharp decline in special education enrollment. Employing a sample of all principals in Texas before and after the 2004 law, this paper examines how the 8.5% cap impacted school leader attrition during its implementation. Prior to the implementation of the cap in 2004, we find little association between the proportion of students receiving services and principal turnover. After its implementation however, we find that principals in schools enrolling more than 8.5% of students in special education had a .39 higher odds ratio of switching districts and a .14 higher odds ratio of exiting the profession. We conclude by highlighting the scarcity of school labor market research that accounts for state-level education policies and note that policy may be more associated with principal turnover than student characteristics themselves.